The Effectiveness of Pregnancy Exercises on the Smoothness of Labor for Mothers Giving Birth at the Serasi Clinic - Srininta Srininta; Mesrida Simarmata; Indra Septiady Manurung; Yarni Kristiani Zai; Yudha Anggriani Putri Nasution (LPPM STIKES KESETIAKAWANAN SOSIAL INDONESIA, 2024)
Childbirth is a series of processes of expelling the fetus, placenta from the uterus to the outside world. Many complications can occur during childbirth due to various factors. HIS. Mal presentation, large fetus, KPD, narrow pelvis, and others. The efforts made are pregnancy exercises, pregnancy exercises so that the mother's body and reproductive organs become more flexible . Objective: To analyze the effectiveness of implementing pregnancy exercises on the smooth delivery process for mothers giving birth at the Serasi Clinic in 2024. Method: This research uses a survey method and a case control research design with a cross sectional design. Population: all mothers giving birth at the Serasi Clinic. Number: i as many as 35 people and with total sampling technique: 35 people. The instrument uses a questionnaire and the data analysis technique uses chi square analysis. Results: The majority of births were smooth, 27 people (77%). as many as 26 people (74%) took part in pregnancy exercise and 1 person (3%) did not take part in pregnancy exercise. Meanwhile, of the 8 people whose labor process was not smooth, 8 people (23%) did not participate in pregnancy exercises. The results of the Chi Square test by looking at the continuity correction obtained a P value of 0.000 (<0.05), so it can be concluded that there is a significant relationship between the implementation of pregnancy exercises and the smoothness of the delivery process at the Serasi Clinic in 2024